PHILOSOPHICAL MODELS OF EXPLAINING HISTORICAL PROCESSES - Abduvohidova , Laziza; Spanov , Meiirkhan (Effective scientific journals, 2025)
Understanding historical processes has always been one of the central problems of philosophy. History is not merely a chronological sequence of events but a complex, multi-layered process shaped by economic, political, cultural, ideological, and spiritual factors. This article provides a comprehensive philosophical analysis of the main models used to explain historical processes. The study examines deterministic, idealistic, materialist (formational), civilizational, cyclical, and postmodern approaches to historical interpretation. Each model is analyzed in terms of its methodological foundations, explanatory power, and limitations. The research argues that no single philosophical model is sufficient to fully explain historical development. Instead, an integrative and pluralistic approach is required to grasp the complexity and multidimensional nature of historical reality. The findings contribute to contemporary debates in the philosophy of history by highlighting the necessity of methodological diversity in historical explanation.